A 4-Day Mindfulness-Based Cognitive Behavioral Intervention Program for CFS/ME. An Open Study, With 1-Year Follow-Up - Stubhaug, Bjarte; Lier, Haldis O.; Aßmus, Jörg; Rongve, Arvid; Kvale, Gerd (Frontiers in Psychiatry, 2018)
Background: Chronic Fatigue Syndrome/Myalgic Encephalopathy (CFS/ME) is an incapacitating illness in which single treatment interventions seem to have variable effects. Based on an earlier study we have conducted a new study with a concentrated intervention program. The aims of this study were to: (1) explore the clinical course for patients with CFS/ME who participated in a treatment program delivered during four consecutive days, and (2) evaluate their satisfaction with this program. Methods: 305 patients diagnosed with CFS/ME (Oxford criteria), recruited from a clinical population referred to a specialist outpatient clinic, participated in an open uncontrolled study of the clinical course through 1 year. The study group participated in a 4-day group intervention program, comprised by education, cognitive group therapy sessions, mindfulness sessions, physical activity and writing sessions, within a context of cognitive behavioral therapy, mindfulness, acceptance and commitment model. Assessments were done by self-reports prior to the first consultation, 1 week before and 1 week after the intervention program, and at 3 months and 1 year after the intervention. SPSS 23 and R 3.3 were used for statistical analyses. The associations between case definitions and the outcome measures (Chalder Fatigue Scale (FS), Short Form 36 (SF-36) physical functioning scale) were assessed by a linear mixed effects model (LME). Results: Results showed statistically significant clinical changes for 80% of the patients after the intervention, changes being sustained through 1 year after the program. For both Fatigue Scale (FS) and the SF-36 there were statistically significant effects of time from baseline to all time points with a statistically significant drop in scores, applying the linear mixed effects model. A subgroup fulfilling the inclusion criteria from the PACE study (Chalder Fatigue Scale >6/11, SF-36 Physical functioning <65/100) showed clinically significant improvement through 1 year, changes in outcome measures were statistically significant (p < 0.001). None of the patients included in the program dropped out, and a great majority of patients expressed high satisfaction with the content, focus and amount of treatment. Conclusion: Clinical changes observed from pre-treatment to 1 year follow-up could represent effects of the 4-day concentrated intervention program, and should be further explored in a controlled study.